PENGARUH PENAMBAHAN POLIETILEN GLIKOL 6000 PADA TABLET IBUPROFEN DISPERSI PADAT TERHADAP ABSORBSI IBUPROFEN SECARA IN SITU - Tampubolon, Antetti (Jurnal Riset Kefarmasian Indonesia, 2021)
Drug absorption can be decided by various methods, namely in vitro methods, in situ methods, and in vivo methods. The in situ method is a procedure that is very close to the in vivo method. The aim of this study was to identify the effect of accumulation of polyethylene glycol 6000 (PEG 6000) on solid dispersion of ibuprofen tablets on the in-situ absorption of the drug. This research was conducted through an experiment to determine the effect of adding polyethylene glycol 6000 to the absorption of ibuprofen in situ by flowing the solution from solid dispersion ibuprofen tablets, solutions from generic ibuprofen tablets and standard ibuprofen solutions. The solid dispersion system was carried out by melting ibuprofen and polyethylene glycol 6000 in a ratio of 1:05. The drug solution was flowed through the lumen of the small intestine of male rats. Unabsorbed ibuprofen was measured by an ultraviolet spectrophotometer at a wavelength of 225.5 nm. Next, the absorbed level of ibuprofen was calculated. The results showed that ibuprofen from solid dispersion tablets was absorbed more than ibuprofen from generic tablets and standard ibuprofen. It can be concluded that polyethylene glycol 6000 has an effect on the absorption of ibuprofen in situ.